1977
DOI: 10.1007/bf01315053
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Aleutian disease virus assayed with feline kidney cells

Abstract: Properties of Aleutian disease virus (ADV) were studied using feline kidney cells, line CRFK, to assay virus by the induction of nuclear antigen. ADV nuclear antigen was detected by immunofluorescent staining. Titers of virus obtained from mink spleens at 10-8 days after infection were usually between 10(3) and 10(5) infectious units per gram of spleen. ADV was purified by fluorocarbon extraction, differential centrifugation, biogel A-15 chromatography and CsCl equilibrium centrifugation. The molecular weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The first scientific evidence of an infectious cause was the demonstration that suspensions of infected mink organs retained their infectivity after filtration, indicating the causative agent was likely viral ( Karstad and Pridham, 1962 ). The virus was subsequently isolated using feline kidney cell lines and it was concluded that it possessed the distinctive properties of a parvovirus ( Hahn et al, 1977 ; Porter et al, 1977 ). The complete genome was sequenced in 1988 ( Bloom et al, 1988 ).…”
Section: Aleutian Mink Disease Virus (Amdv) Discovery and Initial Chamentioning
confidence: 99%
See 1 more Smart Citation
“…The first scientific evidence of an infectious cause was the demonstration that suspensions of infected mink organs retained their infectivity after filtration, indicating the causative agent was likely viral ( Karstad and Pridham, 1962 ). The virus was subsequently isolated using feline kidney cell lines and it was concluded that it possessed the distinctive properties of a parvovirus ( Hahn et al, 1977 ; Porter et al, 1977 ). The complete genome was sequenced in 1988 ( Bloom et al, 1988 ).…”
Section: Aleutian Mink Disease Virus (Amdv) Discovery and Initial Chamentioning
confidence: 99%
“…All bodily fluids (blood, saliva, feces, and urine) can contain viruses and transmission via direct or indirect (contaminated feed, water, or environment) contacts are both possible ( Kenyon et al, 1963 ; Gorham et al, 1964 ; Pennick et al, 2005 ; Shao et al, 2014 ). Virions are highly resistant in the environment and can survive high temperatures and chemical treatments ( Eklund et al, 1968 ; Hahn et al, 1977 ; Porter et al, 1977 ). This stability makes the virus difficult to eliminate from contaminated surfaces and facilitates viral spreading in the wild, and within and between farms ( Prieto et al, 2014 ).…”
Section: Transmission and Host Rangementioning
confidence: 99%
“…+, the restriction enzyme site is present in the sequence; -, the restriction enzyme site is not present in the sequence. (2,16,17,27,38,40) but not to grow productively in CRFK cells (16,28,29,39). Recently, the complete nucleotide sequences of the cell culture-adapted ADV G isolate and the central region of the highly virulent Utah I isolate were reported (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…A characteristic of AD that may contribute to the persistence of the virus is that antiviral antibody is nonneutralizing (18). This phenomenon appears to be a property of the virus and not the host, since antiviral antibody from other infected species also fails to neutralize (9).…”
mentioning
confidence: 99%